Issues of accessibility to health services by older Australians: a review - Deborah van Gaans; Elsa Dent (Frontiers Media S.A., 2018)
Abstract Background This review provides an in-depth investigation into the difficulties facing older Australians when accessing health care services. Methods A literature search was conducted in December 2016 using Academic Premier to identify relevant publications. Key search terms were accessibility, health service, older people and Australia. Papers published between 1999 and 2016 were included. Statements of accessibility were extracted and then grouped using the five dimensions of accessibility by Penchansky and Thomas (1981): availability, accessibility, accommodation, affordability and acceptability. Results Forty-one papers were included. Availability issues identified were inadequate health care services, particularly for culturally and linguistically diverse (CALD) populations and those residing in rural areas. Accessibility issues included difficulties accessing transport to health care services, which in turn restricted choice of appointment time. Issues of accommodation identified were long waiting times for appointments with both general practitioners and medical specialists. Affordability was a common problem, compounded by multi-morbidity requiring high health care use. Issues of acceptability centred on the role of the family, feelings of shame when receiving care from a non-family member, traditional practices and gender sensitivity. Conclusions The contribution of factors to health service accessibility varies according to an older person's geographical local and their accessibility to transport, as well as their level of multi-morbidity and cultural background. Improving access to health services could be improved by matching services to the population that they serve.